Perbandingan Pengaruh dan Perlakuan Akuntansi antara Biaya Bunga dengan Pajak Penghasilan sebagai Bukti Kebenaran Hukum Halal atau Haramnya dalam Perspektif Islam - Rusdin, Muhammad; Farida Aprianti; Irwan Fitri Aco; Asri Asri; Muhammad Faisal Arif (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to determine the comparative effect between interest costs and income tax on sales to achieve the expected profit. Also to determine the comparative accounting treatment between interest costs and income tax in the income statement. The influence and accounting treatment are then used as evidence of the truth of the law of halal or haram in the Islamic perspective. This study is a library research using the analysis method: comparison, qualitative descriptive and quantitative descriptive. The results of the study indicate that interest costs and income tax have an equally large burden because they result in the need for higher sales to achieve the expected profit based on the cost-volume-profit analysis. Based the income statement, interest costs are calculated when there is a profit or loss, so they are more burdensome than income tax which is calculated when there is a profit and not calculated when there is a loss. This influence and accounting treatment prove the truth of the law of halal or haram in the Islamic perspective which has been established approximately thousands of years ago, namely that interest costs are haram so that they are heavier than income tax, the law of which: some argue that it is halal and others argue that it is doubtful, even some argue that it is haram. Based on this, interest costs must be avoided, either as the payer, recipient, witness, clerk or other involvement. Meanwhile, income tax should be complied with sincerely as charity for the payer and the recipient should seek alternative replacements with other sources of income.